Síntese, caracterização e avaliação antimicrobiana de novos derivados do timol e carvacrol - Silva, Gracielle Angeline Tavares da (2018)
By investigating the specialized literature on the vast therapeutic and medical properties regarding the aromatic monoterpenes thymol and carvacrol (antioxidant, anti-inflamatory, antifungal, antitumoral, antibacterial, etc.), it was attempted, in this work, to synthetize a heterologous series of 14 ester derivatives from the intermediate halogens (thymol chloride and carvacrol chloride), containing the chemical groups methylenedioxyphenyl, aromatic ortho-substituted, N-phthalimide, N-phthaloylglycine, terephthalate, aiming at verifying the activity-structure relations of the derivative products in relation to thymol’s and carvacrol’s prototypes. The final derivative products from thymol (DT 1-7) and carvacrol (DC 1-7) were synthetized via a biomolecular nucleophilic substitution reaction (SN2 type) between the thymol and carvacrol halides and carboxylate/imidate anions provenient from the selected salts produced from the carboxylic/imidate-substituted acids ( potassium salts from piperinic acid, benzoic acid, phthalimide, phthaloylglycine and from terephthalic acid) which presented satisfactory relative yield (70% to 90%). In order to confirm which structures were obtained, spectroscopy methods such as IR, 1H-NMR and 13C-EMS were used. The resulting substances were submitted to an in vitro microbiological rehearsal aiming at investigating their anti-fungal pharmacological actions against yeast-like fungi from the Candida sp genus (Candida albicans ATCC-76645 and Candida tropicalis ATCC-13803) and filamentous fungi (Aspergillus fumigatus ATCC-40640 and Aspergillus flavus LM-714), as well as their antibacterial actions against gram-positive strains (Staphylococcus aureus ATCC-1315, M-177) and gram-negative strains (Pseudomonas aeruginosa ATCC-25853 and P-03), by using the micro-dilution technique. In addition, the compounds were submitted to rehearsals in order to determine the antibacterial activity and the drug-resistant modulating activity in Staphylococcus aureus (IS-58), codifying of the efflux protein for tetracycline (Tetk), in which the antibiotic’s MIC was determined in the presence and in the absence of sub-inhibitory concentrations of thymol and carvacrol derivatives. Amongst the final tested products, only the thymolic derivative containing the N-phthaloylglycine nucleus displayed a strong activity against C. albicans (ATCC 76645) and A. flavus (LM-714), whose MIC was equal to 64 μg/mL for both tested strains. DT-4, the carvacrol’s halogenated intermediate, and DC-4 displayed the best anti-staphylococcal activity against Staphylococcus aureus (IS-58), with a MIC of 32, 64 and 32 μg/mL, respectively. Thymol, carvacrol, their respective halogenated intermediates, as well as the final derivative products DT-2, DC-2, DT-3, reduced the MIC of the antibiotic tetracycline (Tetk) by 2. DT-4 and DC-4 displayed the best results by promoting a reduction of up to 32 times, proving to be important compounds to be evaluated in in vivo tests.